Coming Out of War : Poetry, Grieving, and the Culture of the World Wars - Stout, Janis P. (Book collections on Project MUSE., 2005)
While emphasizing aesthetic continuity between the wars, Stout stresses that the poetry that emerged from each displays a greater variety than is usually recognized."--Jacket